Influence of fumaric acid and calcium formate on starter pig performance - L J Kats; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1992)
A 25 d growth trial utilizing 198 pigs was conducted to determine the influence of fumaric acid and calcium formate on starter pig performance. At weaning (19 d of age and 11.9 lb), pigs were blocked by weight and allotted to one of three dietary treatments: a control diet without acid addition or diets containing 1.5% fumaric acid or 1.5% calcium formate. Adding calcium formate to the diet had no influence on average daily gain (ADG), average daily feed intake (ADFI), or feed efficiency (F/G). Pigs fed the diet containing fumaric acid had improved feed efficiency during the first 2 weeks postweaning compared to pigs fed the other two diets. These results do not support the addition of calcium formate to the starter diet. However, results warrant additional research to determine the efficacy of fumaric acid in high nutrient density starter diets.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Starter; Performance; Fumaric acid; Calcium formate